A potential synbiotic beverage from fermented red seaweed (Gracilaria fisheri) using Lactobacillus plantarum DW12 - Hayisama-ae W. (Universiti Putra Malaysia, 2014)
A novel functional beverage was produced from red seaweed (Pom-nang seaweed), by fermentation using a probiotic bacterium Lactobacillus plantarum DW12 as a starter culture. In addition to the normal fermentation products the bacterium produced γ-aminobutyric acid (GABA) and prebiotic compounds. A cell free culture supernatant also inhibited the growth of potential foodborne pathogens and spoilage bacteria (Bacillus cereus TISTR2687, Staphylococcus aureus PSSCMI0004, Escherichia coli PSSCMI0001, Salmonella Typhi ATCC19430 and Vibrio parahaemolyticus PSSCMI0004). In addition, the cell free culture supernatant had antioxidant activity as shown by its ability to scavenge 2, 2/-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) at a level of 60 and 68%, respectively. Using in vitro tests this bacterium was resistant to 1 mM H2O2 for 8 h and grew at various pH values from 2 to 9 and survived for 12 h in the presence of bile salts (0.15-0.30%). Results of antibiotic susceptibility tests showed that 8 of 15 antibiotics were inhibitory to strain DW12 at susceptible and intermediate levels. The fermented red seaweed beverage (FSB) contained 5.41 log CFU/ml lactic acid bacteria, 1284 mg/L GABA, 11.79 mg/ml sugars (fructose, glucose and sucrose) and 0.31 mg/ml of fructooligosaccharides (FOS, kestore and fructosylnystose). Freeze dried FSB at the concentrations tested (0.5-2.0%), that contained 78.61-314.42 mg/100 ml of sugars and 2.10-8.20 mg FOS/100 ml acted as a prebiotic by promoting the growth of strain DW12.